Exploration of combined physical activity and music for patients with Alzheimer’s disease: A systematic review - Li, Kailimi; Cui, CanCan; Zhang, Haipeng; Jia, Luning; Li, Rui; Hu, Hao-Yu (Frontiers in Aging Neuroscience, 2022)
Objective Alzheimer’s disease (AD) can be treated in different ways, one of which is combined physical activity and music intervention, which is a non-pharmacological one. This study provided a thorough systematic review on the application of combined physical activity and music intervention in patients with AD. Method Online sources, such as PubMed, Web of Science, SAGE Premier, EBSCO, and Cochrane, published from January 2002 to March 2022 were searched for articles. Reviewer screened articles on inclusion criteria and identified relevant studies. 200 studies were selected as potentially relevant; of these, eight met all the inclusion criteria. Results The systemic review looked at eight studies, two of which had high methodological quality and six were of moderate quality. Various types of research were included: randomized controlled tails, single-subject study, crossover study, and case report. Music intervention was conducted during an exercise program in six studies. A cognitive stimulation was applied with music therapy and physical activities among two studies. The physical activities or movements included balance training, stretching, strengthening, and different sports activities. Outcome assessment, including the Barthel index in two studies and the functional independence measure, was conducted to evaluate the daily functional score. Mental health was evaluated by Mini-Mental State Examination in three studies. Conclusion Combined physical activity and music intervention are beneficial and improve the cognition, function and well-being of patients with AD. Supporting combined physical and music intervention will play a key role in helping clinical guidelines for both physical therapists and music therapists.